2019
DOI: 10.1111/tpj.14303
|View full text |Cite
|
Sign up to set email alerts
|

Pooled CRISPR/Cas9 reveals redundant roles of plastidial phosphoglycerate kinases in carbon fixation and metabolism

Abstract: Phosphoglycerate kinase (PGK) is a highly conserved reversible enzyme that participates in both glycolysis and photosynthesis. In Arabidopsis thaliana, one cytosolic PGK (PGKc) and two plastidial PGKs (PGKp) are known. It remains debatable whether the two PGKp isozymes are functionally redundant or specialized in plastidial carbon metabolism and fixation. Here, using a pooled clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) strategy, we found that plants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…It is very difficult to directly measure the membrane lipid component contents of chloroplasts isolated from maize anthers by thin layer chromatography and gas-liquid chromatography because of the large amounts of very small anther tissues required for chloroplast extraction (Wang and Benning, 2011;Murphy et al, 2015;Block and Albrieux, 2018). Nonetheless, the MGDG, DGDG, and SQDG contents of whole anther tissue estimated by liquid chromatography-mass spectrometry (Ryu and Wang, 1996;Welti et al, 2002) may be used as an indicator of MGDG, DGDG, and SQDG contents in the membranes of anther En chloroplasts, based on similar results reported recently (Chen et al, 2015;Basnet et al, 2019;Li et al, 2019aLi et al, , 2019bLiu et al, 2020). Therefore, liquid chromatography-mass spectrometry provides us with a good opportunity to explore the function of ZmMs33 in anther chloroplast development and function.…”
Section: Loss Of Zmms33 Function Causes H 2 O 2 Accumulation Inmentioning
confidence: 66%
See 1 more Smart Citation
“…It is very difficult to directly measure the membrane lipid component contents of chloroplasts isolated from maize anthers by thin layer chromatography and gas-liquid chromatography because of the large amounts of very small anther tissues required for chloroplast extraction (Wang and Benning, 2011;Murphy et al, 2015;Block and Albrieux, 2018). Nonetheless, the MGDG, DGDG, and SQDG contents of whole anther tissue estimated by liquid chromatography-mass spectrometry (Ryu and Wang, 1996;Welti et al, 2002) may be used as an indicator of MGDG, DGDG, and SQDG contents in the membranes of anther En chloroplasts, based on similar results reported recently (Chen et al, 2015;Basnet et al, 2019;Li et al, 2019aLi et al, , 2019bLiu et al, 2020). Therefore, liquid chromatography-mass spectrometry provides us with a good opportunity to explore the function of ZmMs33 in anther chloroplast development and function.…”
Section: Loss Of Zmms33 Function Causes H 2 O 2 Accumulation Inmentioning
confidence: 66%
“…For example, Multiple Archesporial Cell 1 (MAC1) , Male Sterile Converted Anther 1 (MSCA1) (Kelliher and Walbot, 2012), Male Sterility 23 (Ms23) (Nan et al, 2017), Ms32 (Moon et al, 2013), and Out Cell Layer 4 (OCL4) (Vernoud et al, 2009) participate in premeiotic morphogenesis, and Abnormal Pollen Vacuolation 1 (APV1) (Somaratne et al, 2017), ZmMs7 (Zhang et al, 2018;An et al, 2020), Irregular Pollen Exine 1 (IPE1)/ZmMs20 (Chen et al, 2017;Wang et al, 2019), Ms26 (Djukanovic et al, 2013), ZmMs30 (An et al, 2019), ZmMs33 (Xie et al, 2018;Zhu et al, 2019), ms44 (Fox et al, 2017), Ms45 (Cigan et al, 2001), and Ms6021 (Tian et al, 2017) are required for anther development and pollen formation during the meiotic and postmeiotic stages in maize. In addition, non-coding RNAs (e.g., miRNAs and ceRNAs) are also involved in maize anther development and pollen formation (Li et al, 2019a(Li et al, , 2019b. Nevertheless, little is known about the metabolic mechanisms that underlie male sterility in maize or about the changes in production, distribution, and utilization of energy and nutrients (e.g., saccharides, lipids, and proteins) that ultimately result in male sterility of GMS mutant anthers.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of glycolytic enzymes caused by the expression of BnLACS2 in yeast prompted us to then detect whether these genes were altered in BnLACS2 transgenic rapeseed plants. qRT-PCR analysis revealed that the expression of genes for key glycolytic enzymes, including phosphofructokinase (PFK), phosphoglycerate kinase (PGK), enolase (ENO) and pyruvate kinase (PYK) [36][37][38] were significantly increased in BnLACS2-OE transgenic plants, while the expression of those genes were decreased in BnLACS2-RNAi transgenic plants, compared to non-transgenic plants (Fig. 7).…”
Section: Bnlacs2 Overexpression Influences the Expression Of Genes Inmentioning
confidence: 99%
“…For multiplex, more than two sgRNA expression cassettes could be assembled in each of these vectors (Du et al, 2016;Do et al, 2019). Usually, a number of engineered editing reagents for ZFNs, TELENs, or CRISPR/Cas systems, does not show editing activity and cannot create any mutation event in vivo without knowing any cause (Li R. et al, 2019). Therefore, identification of mutations in vivo by validating sgRNA expression and nuclease activity for specific editing reagents via transient assay could save time and resources, and increase success rate before transformation for creating genome edited plants (Do et al, 2019;Bai et al, 2020).…”
Section: Gmu6mentioning
confidence: 99%
“…PCR/RE assay detection method was used frequently in soybean (Michno et al, 2015;Sun et al, 2015;Kanazashi et al, 2018;Di et al, 2019). T7EI assay was occasionally used (Cai et al, 2015;Du et al, 2016) and PCR/Sequencing assay is now the most popular method used to detect mutation in soybean (Haun et al, 2014;Campbell et al, 2019;Cheng et al, 2019;Do et al, 2019;Han et al, 2019;Li R. et al, 2019;Wang J. et al, 2020). PCR/RE and T7EI are cost efficient method when large number putative mutations need to be screened, but limitation of restriction enzyme cut sites can restrict design of sgRNA.…”
Section: Screening Of Mutation Events Created By Ge (Figures 2l-m)mentioning
confidence: 99%